(untitled) (Ius Novum, 2019)
The article aims to present the tax-related consequences (with respect to VAT) of typical, and also less common, legal and physical transactions between partners of a partnership and a partnership itself. From the perspective of commercial partnerships and companies law or, in the broadest approach, civil law, these are in general activities that are very well defined by the representatives and commentators of the legal doctrine. However, the performance of the said activities quite often results in tax consequences, in particular in the sphere of income tax, tax on civil-law transactions as well as VAT. In the case of VAT, it seems, the consequences are the least predictable. Thus, the conclusion is obvious: in many situations, steps that partners take at the stage of setting up a partnership, in the course of its operations and liquidation can result in unsatisfactory effects if the obligation with regard to VAT is not properly recognised.